Structural diversities in centrosymmetric La8S4Cl8La12S8Cl4[SbS3]8 and non-centrosymmetric Ln12S8Cl8[SbS3]4 (Ln = La and Ce): syntheses, crystal and electronic structures, and optical properties. Issue 6 (22nd January 2021) - Zhao, Hua-Jun; Liu, Peng-Fei; Wu, Li-Ming
Abstract : Three thioantimonides charge compensated by Ln/S/Cl cationic layers, namely centrosymmetric La8 S4 Cl8 La12 S8 Cl4 [SbS3 ]8 and non-centrosymmetric Ln12 S8 Cl8 [SbS3 ]4 (Ln = La and Ce) have been discovered for the first time. Abstract : Three thioantimonides charge compensated by Ln/S/Cl cationic layers, namely, La8 S4 Cl8 La12 S8 Cl4 [SbS3 ]8 and Ln12 S8 Cl8 [SbS3 ]4 (Ln = La and Ce), have been discovered by conventional solid-state reactions. The former crystallizes in the centrosymmetric space group Pbcm (no. 57), while the latter adopts the polar non-centrosymmetric space group Cc (no. 9). Both of them contain isolated SbS3 trigonal-pyramidal units, which are connected either with the alternating centric [La8 S4 Cl8 ] 8+ and mirror-symmetric [La12 S8 Cl4 ] 16+ cationic layers perpendicular to the [001] direction in La8 S4 Cl8 La12 S8 Cl4 [SbS3 ]8 or with the acentric [Ln12 S8 Cl8 ] 12+ cationic layers perpendicular to the [100] direction in Ln12 S8 Cl8 [SbS3 ]4 . Interestingly, the discrete SbS3 trigonal pyramids pack in a centrosymmetric and non-centrosymmetric fashion in La8 S4 Cl8 La12 S8 Cl4 [SbS3 ]8 and La12 S8 Cl8 [SbS3 ]4, respectively, which can be ascribed to the different compositions and packing fashions in Ln/S/Cl cationic layers. In addition, optical gaps of 2.31 and 2.60 eV for La12 S8 Cl8 [SbS3 ]4 and La8 S4 Cl8 La12 S8 Cl4 [SbS3 ]8, respectively, were determined by UV/vis reflectance spectroscopy, showing a blue shift with respect to La7 Sb9 S24, which can be attributed to the greater contributions of La to the bottom of the CB as confirmed by the DFT study.